2021
DOI: 10.1186/s12872-021-02391-x
|View full text |Cite
|
Sign up to set email alerts
|

U-shaped relationship between platelet–lymphocyte ratio and postoperative in-hospital mortality in patients with type A acute aortic dissection

Abstract: Background The platelet-lymphocyte ratio (PLR), a novel inflammatory marker, is generally associated with increased in-hospital mortality risk. We aimed to investigate the association between PLR and postoperative in-hospital mortality risk in patients with type A acute aortic dissection (AAAD). Methods Patients (n = 270) who underwent emergency surgery for AAAD at Xiangya Hospital of Central South University between January 2014 and May 2019 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…A previous study from our group indicated that low platelet count was a risk factor of postoperative pneumonia in AAAD patients, possibly due to platelet activation and high consumption (2). Besides, we found a U-shaped relationship between platelet-lymphocyte ratio and in-hospital mortality in patients with AAAD (22), which also revealed a role for platelets in poor prognosis. In the present study, our findings manifested that PDW was positively correlated with the risk of postoperative pneumonia, supporting our previous conjecture.…”
Section: Discussionsupporting
confidence: 70%
“…A previous study from our group indicated that low platelet count was a risk factor of postoperative pneumonia in AAAD patients, possibly due to platelet activation and high consumption (2). Besides, we found a U-shaped relationship between platelet-lymphocyte ratio and in-hospital mortality in patients with AAAD (22), which also revealed a role for platelets in poor prognosis. In the present study, our findings manifested that PDW was positively correlated with the risk of postoperative pneumonia, supporting our previous conjecture.…”
Section: Discussionsupporting
confidence: 70%
“…Generally, a higher NLR value and a higher PLR value have been correlated with high mortality and poor prognosis in non-healthy populations [ 27 , 28 , 29 , 30 ]. However, in the general, healthy population there are not yet standardized values for a normal range of NLR and PLR values that consider various modifiable and nonmodifiable factors.…”
Section: Discussionmentioning
confidence: 99%
“…13 Relationships between platelet ratio and chronic obstructive pulmonary disease, acute aortic dissection, peritoneal dialysis, haemodialysis, and severe pneumonia have been reported in numerous studies. [14][15][16][17][18] Decreased platelet count in severe disease is a predictor of mortality. 19 This suggests that platelet ratio may be used as a tool for predicting the prognosis of patients with AMI.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Studies have shown that platelets are markers of chronic inflammation and are associated with poor clinical outcomes in various cardiovascular diseases 13. Relationships between platelet ratio and chronic obstructive pulmonary disease, acute aortic dissection, peritoneal dialysis, haemodialysis, and severe pneumonia have been reported in numerous studies 14–18. Decreased platelet count in severe disease is a predictor of mortality 19.…”
Section: Introductionmentioning
confidence: 99%